A SERIES OF SIMPLE DECONTAMINATION METHODS OF BACTERIAL FLORA FOUND ON MUSICAL WIND INSTRUMENTS - KUSUMA, SRI AGUNG FITRI; SARI, WAHYU PURWITA; RUSMIATI, DEWI (International Journal of Applied Pharmaceutics, 2022)
Objective: This study was aimed to compare the efficacy of cleaning techniques using hot water treatment soap containing 2% triclosan and chemical antiseptics in reducing the bacterial contamination observed on shared musical wind instruments. Methods: The trumpet, mellophone, trombone, and tuba were evaluated in this study. To count the initial bacterial colonies on the instrument, the total amount of bacteria adhered to it was extracted using the swab procedure. The mouthpieces were immersed in hot water at a temperature of 100 °C for 5 min and then were soaked in soap that contained 2% triclosan to achieve the effect of decontamination. Then the survival colonies were counted. As a series of decontamination technique, this study also examined the disinfection ability of phenol, chloroxylenol, povidone-iodine, and 70% alcohol utilizing the Rideal Walker method. Results: When compared to liquid soap (50.30-91.67%), the cleaning procedure that uses immersion in hot water of 100 °C for 5 min greatly lowers the quantity of bacteria (91.85-99.91%). However, due to their huge surface area, tuba mouthpieces were the most straightforward to sterilize using both techniques. The highest phenol coefficient value was shown by chloroxylenol; however, all tested disinfectants showed stronger antibacterial activity than 1% phenol. Conclusion: The mouthpieces of shared wind instruments can be cleaned quickly, easily, and effectively by immersing them in hot water at a temperature of 100 °C for 5 min. However, chloroxylenol has the strongest ability to eradicate bacteria from the instrument's mouthpiece.